Deer Forests, Landlords, and Crofters: The Western Highlands in Victorian and Edwardian Times - Bumsted, J.m. (Labour / Le Travail, 1984)
This article reviews the book, "Deer Forests, Landlords, and Crofters: The Western Highlands in Victorian and Edwardian Times", by Willie Orr.